Effects of α-Mangostin on Viability, Growth and Cohesion of Multicellular Spheroids Derived from Human Breast Cancer Cell Lines - Scolamiero, Giuseppe (Int J Med Sci, 2018)
Background: α-Mangostin (αMG) is extracted from Garcinia mangostana Linn and exerts antiproliferative activities. Although several researches on αMG were performed using cell monolayers, the in vitro pharmacological effects on 3D cancer models have never been investigated. Aim of the present study was to find new anticancer properties of αMG by evaluating the changes that this compound provokes in multicellular tumour spheroids (MCTSs). Methods: MCTSs were generated from MDA-MB-231 and MCF-7 breast tumour cell lines and then treated with 0.1÷30 μg/ml αMG for 24 and 48 h. MCTS size, density, and cell migration were determined by software elaboration of phase contrast images captured by a digital camera. Cell viability was evaluated by resazurin and acid phosphatase assays, while cell apoptosis was assessed by a fluorescent assay of caspase activity. The distribution of living cells inside MCTSs was shown by live/dead fluorescence staining. Results: A dose-dependent decrease in cell viability was obtained by treating MDA-MB-231 spheroids with αMG for 48 h (IC(50) = 0.70-1.25 μg/ml). A significant reduction in spheroid volume, paralleled by its increased compactness, was observed only at concentration of 30 μg/ml, but not with lower doses of αMG. By contrast, αMG in the range of 5-15 μg/ml increased the size of MCTSs due to a parallel reduction in cell aggregation. The same window of concentrations was also able to stimulate cell apoptosis in a dose-dependent manner. Bimodal volumetric effects were also obtained by treating the spheroids generated from the MCF-7 cells with 0.1÷30 μg/ml αMG for 48 h. Finally, doses higher than 5 μg/ml caused a progressive impairment in cell migration from the edge of MDA-MB-231 MCTSs. Conclusion: After exposure at doses of αMG just above IC(50), MDA-MB-231 spheroids showed a significant reduction in cell adhesion that did not stimulate cell migration but, on the contrary, blunted cell motility. These findings suggest a novel anticancer feature of αMG that could be taken into consideration to improve conventional drug penetration into the tumour bulk.